Hygrocybe rimosa (Hygrophoraceae, Agaricales), a new poisonous species from southern China - Wang, Chao-Qun; Zhang, Ming; Li, Hai-Jiao; Huang, Hao; Deng, Wang-Qiu; Li, Ting; Luo, De-Jun; Li, Tai-Hui (Phytotaxa, 2021)
Hygrocybe rimosa, a new poisonous species belonging to subg. Hygrocybe, is described from southern China with both phylogenetic and morphological data. This species can cause nausea, vomiting, and abdominal pain. Morphologically, it is characterized by its orange to red and fibrillose pileus, irregularly split pileus margin, free, broad to ventricose, white lamellae, and subglobose to oblong basidiospores measuring (7)7.5–11 ×5–8(8.5) μm. Phylogenetically, analyses based on the internal transcribed spacer (ITS) region and the nuclear ribosomal RNA large subunit (LSU) indicate that H. rimosa is a member of subg. Hygrocybe. Ecologically, the new taxon usually grows in subtropical grasslands.